Causal relation – condition of parents’ liability for damage caused by minors or minors - Hlushchenko , Inna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article highlights the problem of parents' responsibility for the actions of minors. In particular, attention is drawn to the fact that the tort law of Ukraine applies the general principle of liability for fault, along with this, as an exception, the law foresees the possibility of imposing liability on the person who caused the damage without fault. The fault of the parents of minors or minors who caused damage has its own characteristics and, in our opinion, should be considered careless. After all, even if the parents deliberately left their minor or underage children unattended, or led an immoral lifestyle, the parents did not cause harm directly. The above actions of the parents were mostly aimed not at causing harm to another person, but at the improper performance of parenthood in relation to the upbringing and maintenance of minors or minors. That is why the article talks about the cause-and-effect relationship of the fault of the parents and/or the educational institution as a subsidiary and solidarity obligation. At the same time, the principle of culpability is expressed not in the fact that parents, given the actual distance of separate residence from their children, are exempted from responsibility in the absence of their fault, but in the fact that they are responsible for failure to fulfill their parental duties. Attention is drawn to the fact that the responsibility of parents should not be considered as a penalty for the actions of minors or minors. Such liability should be considered as a guarantee for the injured party, in particular a guarantee that the damages caused to him will be compensated, and the guilty parties will still be held responsible. Judicial practice is analyzed and attention is drawn to the subordinate nature of the responsibility of parents (educational institution) only in the event that a minor does not have sufficient property to compensate for the damage caused by him. It is argued that the cause-and-effect relationship is important and is the main condition for imposing on the delinquent the obligation to compensate the damage caused by a minor or minor.